Teaching the basic concepts of the Special Relativity in the secondary school in the framework of the Theory of Conceptual Fields of Vergnaud - Otero, María Rita (2015)
In this work, we investigate the conceptualization of the basic aspects of Special Relativity (SR) at secondary school level. We have conducted our research along the lines of the Theory of Conceptual Fields (TCF) proposed by Vergnaud (Vergnaud G., Infancia y Aprendizaje, 36 (2013) 131). The investigation consisted in the design, implementation and evaluation of a didactic sequence specially elaborated to conceptualize the basic aspects of SR. The proposal is composed by eight situations, complemented with a set of exercises. It was carried out in two classrooms with students of the last year of secondary level (17 years old, N = 43). The conceptualization was analyzed in a classroom context, where the selected situations are essential to promote the emergence of the relevant concepts.